Individual and Combinatorial Antibacterial Properties of Plectranthus amboibicus, Murraya koenigii, Acorus calamus and Azadiractha indica Against Acne Causing Bacteria Staphylococcus aureus, Propionibcaterium acnes and Staphylococcus epidermidis - Krishnasamy, Sharanya Laxme (2015)
Bacteria have developed resistance against various antibiotics. The aim of this study is to test for antibacterial properties of Murraya koenigii, Plectranthus amboinicus, Azadirachta indica and Aconis calarnus crude extracts against clinically important bacteria Staphylococcus aurcus, Sraphyloccocus epidermidis and Propionibacterium acnes. A preliminary test was done to test individual and also combinatorial ethanolic extract formulas using the disk diffusion assay and agar diffusion assay against the pure bacterial cultures and also acne samples that had been obtained with the consent of volunteers. The disk diffusion assay carried out allowed less amount of extracts of M. koenigii. P. amboinicus, A. indica and A. calamus compared to the agar diffusion assay. The negative control used was 80% ethanol to confirm that the ethanol in the extraction preparation did not affect the antibacterial activity. It was noticed that all four extracts had antibacterial activity. However, in combination with A. calamus, there is an antagonistic effect that decreases the diameter of the zone of inhibition produced. The combination of M. koenigii and A. indica showed promising results and was further tested against pure bacterial cultures and acne sample cultures and provided a rather satisfying zone of inhibition for several sample especially Acne sample 5. Each combination of extract had different effect on different bacteria. ANOVA analysis also showed the mean difference is significant at the 0.05 levcl for P. acnes, Acne sample 5, 6, and 7 where else no significance was generated at 0.05 Level for S. aureus, S. epidermidis and Acne sample 4. The tests also suggested that for topical application of these antibacterial agents, the crude plant extracts are best individually and not in combination.